Distinctive pattern of expression of spermatogenic molecular markers in testes of azoospermic men with non-mosaic Klinefelter syndrome - Kleiman, Sandra E. (J Assist Reprod Genet, 2016)
PURPOSE: Mature sperm cells can be found in testicular specimens extracted from azoospermic men with non-mosaic Klinefelter syndrome (KS). The present study evaluates the expression of various known molecular markers of spermatogenesis in a population of men with KS and assesses the ability of those markers to predict spermatogenesis. METHODS: Two groups of men with non-obstructive azoospermia who underwent testicular sperm-retrieval procedures were included in the study: 31 had non-mosaic KS (KS group) and 91 had normal karyotype (NK group). Each group was subdivided into mixed atrophy (containing some mature sperm cells) or Sertoli cell only syndrome according to testicular histology and cytology observations. Semi-quantitative histological morphometric analysis (interstitial hyperplasia and hyalinization, tubules with cells and abnormal thickness of the basement membrane) and expression of spermatogenetic markers (DAZ, RBM, BOLL, and CDY1) were evaluated and compared among those subgroups. RESULTS: Clear differences in the histological morphometry and spermatogenetic marker expression were noted between the KS and NK groups. There was a significant difference in the expression of spermatogenetic markers between the subgroups of the NK group (as expected), while no difference could be discerned between the two subgroups in the KS group. CONCLUSION: We conclude that molecular spermatogenetic markers have a pattern of expression in men with KS that is distinctively different from that of men with NK, and that it precludes and limits their use for predicting spermatogenesis in the former. It is suggested that this difference might be due to the specific highly abnormal histological morphometric parameters in KS specimens. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10815-016-0698-0) contains supplementary material, which is available to authorized users.